Price coordination in two-sided markets: Competition in the TV industry - Hans Jarle Kind; Tore Nilssen; Lars Sørgard (Center for Economic Studies and ifo Institute (CESifo), 2010)
The TV industry is a two-sided market where both advertisers and viewers buy access to the programs offered by competing TV channels. Under the current market structure advertising prices are typically set by TV channels while viewer prices are set by distributors (e.g. cable operators). The latter implies that the distributors partly internalize the competition between the TV channels, since they take into account the fact that a lower viewer price at one channel will harm rival channels. We nonetheless find that a shift to a market structure where both advertising prices and viewer prices are set competitively by the TV channels might increase joint industry profits. The reason is that this market structure, in contrast to the one we observe today, directly addresses the two-sidedness of the market. We also show that this is to the benefit for the viewers.
Keywords: D40; D62; L10; L82; 330; price coordination; two-sided markets; media economics; Fernsehanstalt; Fernsehwerbung; Private Fernsehanstalt; Betriebliche Preispolitik; Preiswettbewerb; Marktstruktur; Theorie